Advanced head and neck cancer in older adults: Results of a short course accelerated radiotherapy trial. Issue 3 (April 2021) - Ferro, Milena; Macchia, Gabriella; Re, Alessia; Buwenge, Milly; Ferro, Marica; Boccardi, Mariangela; Picardi, Vincenzo; Ianiro, Anna; Arena, Eleonora; Zamagni, Alice; Farina, Eleonora; Cilla, Savino; et al.
Abstract: Objectives: To assess the feasibility and safety of a repeated SHort course Accelerated RadiatiON therapy (SHARON) regimen in the palliative setting of Head and Neck (H&N) cancer in older adults. Material and Methods: Patients with histological confirmed H&N cancers, age ≥ 80 years, expected survival >3 months, and Eastern Cooperative Oncology Group (ECOG) performance status of ≤3 were enrolled. Patients were treated in cohorts of six patients: a total dose of 20 Gy was delivered in 2 consecutive days with a twice-daily fractionation (5 Gy per fraction) and at least 8-h interval. If no Grade 3 toxicity was registered, a second enrollment started with another cohort of six patients to whom were administered two cycles (total dose of 40 Gy). The primary endpoint was to evaluate the feasibility of the two cycles of treatment. Secondary endpoints were evaluation of symptoms control rate, symptoms-free survival (SFS), and Quality of Life (QoL) scores. Results: Seventeen consecutive patients (median age: 85 years) were treated. Nine patients were treated with one cycle and 8 patients with two cycles. No G3 toxicity was reported in either cohort. With a median follow-up time of 4 months, 3-month SFS in the first and second cohorts was 83.3%, and 87.5%, respectively. The overall palliative response rate was 88%. Among 13 patients reporting pain, 8 (61.5%) showed an improvement or resolution of their pain. Conclusion: Repeated short course accelerated radiotherapy in a palliative setting of H&N cancers is safe and well-tolerated in older adults.